The Influence of Contextual Teaching and Learning (CTL) Learning Model on 21st Century Skills of Students in Class X Biology Learning - Enicgia Shantia; Lufri Lufri (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The low 21st century skills of students in learning biology, because the learning process is still teacher-centered, teachers are still dominant in applying conventional learning. Efforts that can be made to overcome these problems are by applying the Contextual Teaching and Learning (CTL) model. The purpose of this study was to see the effect of the CTL model on the 21st Century skills of students. This research is quasi-experimental research. The population of this study were students of class X SMAN 12 Kerinci. Hypothesis test data analysis was carried out using the t-test. The results showed that the value of 21st Century skills of students in learning biology material, ecology and environmental change in the experimental class was higher than the control class. The average value of 21st Century skills of students which includes (a) Critical thinking skills in the experimental class were obtained 72.04 while the control class was obtained 61.13. (b) Communication skills in the experimental class obtained 75.90 while the control class obtained 68.06. (c) Collaboration skills in the experimental class obtained 79.81 while the control class obtained 68.79. (d) Creativity skills in the experimental class obtained 79.92 while the control class obtained 72.73. So, So, it can be concluded that applying the CTL learning model can significantly improve the 21st century skills of students.Abstrak: Rendahnya keterampilan abad 21 siswa dalam pembelajaran biologi, karena proses pembelajaran masih berpusat pada guru, guru masih dominan dalam menerapkan pembelajaran konvensional. Upaya yang dapat dilakukan untuk mengatasi permasalahan tersebut adalah dengan menerapkan model Contextual Teaching and Learning (CTL). Tujuan penelitian ini adalah untuk melihat pengaruh model CTL terhadap keterampilan abad 21 siswa. Penelitian ini merupakan penelitian eksperimen semu. Populasi penelitian ini adalah siswa kelas X SMAN 12 Kerinci. Analisis data uji hipotesis dilakukan dengan menggunakan uji-t. Hasil penelitian menunjukkan bahwa nilai keterampilan abad 21 siswa dalam pembelajaran materi biologi, ekologi dan perubahan lingkungan pada kelas eksperimen lebih tinggi daripada kelas kontrol. Nilai rata-rata keterampilan abad 21 siswa meliputi (a) Keterampilan berpikir kritis pada kelas eksperimen diperoleh 72,04 sedangkan kelas kontrol diperoleh 61,13; (b) keterampilan komunikasi pada kelas eksperimen diperoleh 75,90, sedangkan pada kelas kontrol diperoleh 68,06; (c) Keterampilan kolaborasi pada kelas eksperimen diperoleh 79,81 sedangkan pada kelas kontrol diperoleh 68,79d) keterampilan kreativitas pada kelas eksperimen diperoleh 79,92 sedangkan pada kelas kontrol diperoleh 72,73. Jadi, dapat disimpulkan bahwa penerapan model pembelajaran CTL dapat meningkatkan keterampilan abad 21 siswa secara signifikan.